Evaluation of the acoustic emission monitoring method for stress corrosion cracking on aboveground storage tank floor steel. (January 2020) - Bi, Haisheng; Li, Huiyao; Zhang, Wei; Wang, Lin; Zhang, Qinglei; Cao, Suzhen; Toku-Gyamerah, Isaac
Abstract: Stress corrosion cracking (SCC), which is one of the main threats to the structural integrity of aboveground storage tanks (ASTs), has recently attracted much attention. In this paper, the SCC of the storage tank floor was studied by the acoustic emission (AE) and electrochemical methods. Throughout the whole SCC process, the AE signal characteristic parameters, cumulating features, and correlations were analyzed, and the signal time-frequency local features were extracted via wavelet packet analysis based on the MATLAB program. A good correlation of the instantaneous variations between the AE activity and the corrosion behavior was found. Microcrack creeping and macrocrack propagation were the most important AE sources in SCC; these sources can be recognized by the AE parameters and the AE frequency spectrum. The results in this paper will be beneficial for the diagnosis of corrosion severity and the recognition of the corrosion sources by AE online inspection and will further provide an assessment of the AST integrity by means of a risk-based inspection technique. Highlights: Aboveground storage tank (AST) is currently widely used in petrochemical industries all over the world. It plays an irreplaceable role in oil and oil derivatives storage and transportation system. However, it is now being threatened by tank bottom corrosion which leads to leakage and firing in recent decades. On one hand, the storage medium becomes more salty and higher water cut, on the other hand, a part of storage tanks are nearing the end of their service lives. Besides the common types of pitting and uniform corrosion, the stress corrosion cracking (SCC) also cannot be neglected in AST bottom damage, SCC is one of the most critical corrosion types that can lead to premature catastrophic failures of structural components. In this paper we focuses on the characterization of storage tank floor SCC using acoustic emission (AE) on-line monitoring technology and electrochemical polarization in situ measurement technology. The AE signal characteristic parameters cumulated features and correlations are analyzed throughout the entire process of SCC, and signal time-frequency local features are extracted via wavelet analysis based on the Matlab programming.